Effectiveness of Frankl's Logotherapy on Health (Decreasing Addiction Potential and Increasing Psychological Well-being) of Students with Depression - Paridokht Esalati; Ali Arab; Vali Mehdinezhad (Iranian Association of Health Education and Health Promotion, 2019)
Background and Objective: Depression is one of the most common psychological problems that can increase addiction potential and decrease psychological well-being. There are different methods to improve the psychological status of people and logotherapy is one of them. As a result, present research aims to determine effectiveness of Frankl's logotherapy on addiction potential and psychological well-being of girl students with depression. Methods: This was a semi-experimental study with a pre-test and post-test design. The research population included girl students with depression in Farhangian University of Birjand Pardis in the 2017-18 academic years. 30 people were selected via available sampling method and were randomly assigned to two equal groups. The experimental group was trained for 8 sessions of 90 minutes (twice a week) using Frankl's logotherapy method. The instruments included the questionnaires of depression, addiction potential, and psychological well-being. The data were analyzed using t-test and MANCOVA methods. Results: The findings showed that there was a significant difference between the two groups in terms of addiction potential and psychological well-being. In the other words, the Frankl's logotherapy significantly led to decreased addiction potential (F=57/10, P<0/001) and increased psychological well-being (F=73/36, P<0/001) of girl students with depression. Conclusion: The results indicated the effectiveness of Frankl's logotherapy on decreasing addiction potential and increasing psychological well-being. Therefore, counselors and therapists can use Frankl's logotherapy method to decrease addiction potential and increase psychological well-being of girl students with depression.